Strategies For Teaching Reading In Efl Classroom - Ratna Nidya Primasari; Chyntia Heru Woro Prastiwi; Oktha Ika Rahmawati (Universitas Muhammadiyah Semarang, 2022)
Reading for junior high school students becomes a fundamental skill because they will use it for further studies at senior high school and university levels. Teaching reading requires various good strategies to arouse students’ motivation and optimize learning outcomes. This descriptive qualitative study investigated strategies used by two English teachers in grades seven and eight at SMPN 2 Bojonegoro, specifically in teaching descriptive and recount texts. The data derived from four reading class meetings were analyzed using an observation checklist and interviews. The results of the study demonstrated that there were 3 strategies used by the teachers, namely RCRR (Read Cover, Remember, Retell), CSR (Collaborative Strategic Reading), and translation. The first two strategies were often applied in grade eight as they were sequential and good for active learners. Meanwhile, translation became the appropriate strategy for grade seven as they had limited vocabulary and were still passive learners. By using numerous reading strategies, it is expected that the students can more easily understand the reading texts. Reading strategies provide students with the tools needed to become aware of their thinking, gain confidence in their ability to think and analyze texts, encounter barriers to comprehending text, and most importantly, make thinking visible and audible.